Synthesis of 8-Bromo-7-chloro[1,2,4]triazolo[4,3-c]pyrimidines, Their Ring Rearrangement to [1,5-c] Analogues, and Further Diversification - Tang, Caifei; Wang, Chao; Li, Zhiming; Wang, Quanrui (Synthesis, 2014)
8-Bromo-7-chloro[1,2,4]triazolo[4,3-c]pyrimidines were prepared by bromine-mediated oxidative cyclization of the aldehyde-derived hydrazones. The structure of one such product was unambiguously confirmed by single-crystal X-ray analysis. While the C-5 unsubstituted 1,2,4-triazolo[4,3-c]pyrimidine chemotype is extremely susceptible to ring isomerization at ambient conditions, the C-5-substituted analogues were found to be quite stable, permitting isolation in pure form. Nevertheless, they can still be converted into the 1,2,4-triazolo[1,5-c]pyrimidines by base- or acid-promoted Dimroth rearrangement. The presence of halogen functionalities on the pyrimidine nucleus renders the products useful as versatile synthetic intermediates for the easy diversification, as evidenced by palladium-catalyzed Kumada cross-couplings and Buchwald–Hartwig amination, as well as direct aromatic substitution.
Keywords: hydrazones; oxidation; nitrogen heterocycles; triazolopyrimidines; rearrangement